Каравай: рассказы / Павел Гоголев - Гоголев Павел Петрович (Шелест, 2021)
Экземпляры: КР (20211208) / Инвентарный номер: 1115882 / Цена: / Сис.шифр: 84(2) / Авт.знак: Г 58 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-4